Maternal behavioural determinants and livestock ownership are associated with animal source food consumption among young children during fasting in rural Ethiopia - Kim, Sunny S.; Nguyen, Phuong Hong; Tran, Lan Mai; Abebe, Yewelsew; Asrat, Yonas; Tharaney, Manisha; Menon, Purnima (John Wiley & Sons, 2019)
Religious fasting often involves abstention from animal source foods (ASFs). Although children are exempt, their diets are influenced by the widespread fasting practices. This study investigated the factors influencing ASF consumption among young children during the Lent fasting period in western Amhara, Ethiopia. We used baseline survey data from households with children 6–23 months of age (n = 2,646). We conducted regression analysis to examine the maternal and household factors associated with ASF consumption and path analysis to examine the direct and indirect effects of maternal knowledge, beliefs, social norms, and livestock ownership on ASF consumption. Only 24% of children consumed any ASF in the previous day—18% dairy products, 5% eggs, and 2% flesh foods. Mothers with high knowledge, beliefs, and social norms about feeding children ASFs during fasting had higher odds (odds ratio: 1.3–1.4) of children who consumed them. Compared with households with no ASFs, those with ASFs available were 4.8 times more likely to have children who consumed them. Most of the association between knowledge, beliefs and social norms, and ASF consumption was explained by pathways operating through ASF availability (approximately 9, 12, and 8 pp higher availability, respectively), which in turn were associated with higher consumption. Cow ownership was directly and indirectly associated with ASF consumption, whereas having chickens was indirectly associated with consumption via the availability pathway. Our findings corroborate the importance of maternal behavioural determinants related to feeding ASFs to children during fasting on ASF consumption via household availability and the positive influence of livestock ownership.